Impact of the emigration of nurses on health care delivery system in selected hospitals, Benin-City, Edo State, Nigeria - Olaolorunpo OLORUNFEMI; David Idenyi AGBO; Omotayo Mercy OLORUNFEMI; Esther Odogho OKUPAPAT (Wolters Kluwer Medknow Publications, 2020)
Background: Globally, there is a high demand for nurses, resulting in migration from low-to high-income countries. The emigration of nurses is the act of leaving one's own country to settle permanently in another country, leading to a shortage in the number of nurses in their home countries. Consequently, this study aims to assess the impact of the emigration of nurses on the health-care delivery system in Nigeria. Materials and Methods: A descriptive cross-sectional survey was conducted with a stratified sampling technique to select 270 nurses from three selected hospitals in Benin-city Edo state. A self-structured questionnaire with open and Likert scale questions were used as an instrument to assess the Impact of the Emigration of nurses on the Health Care Delivery System. Data collected were analyzed using tables, percentages, means, standard deviation and t-test. Results: The result showed a mean score of 1.59 ± 0.92 impacts of the emigration of nurses on health-care delivery system and identified how to reduce it. The study also showed that there is no significant difference between gender and reason for emigration among nurses (t = 3.84, P ≤ 0.001). Conclusion: The emigration of nurses is severely affecting the health care delivery system in the country. Recently, the Nursing and Midwifery Council of Nigeria gave the directive for training schools to increase their training capacity and number of students' intake to cushion the effect, and this study shows that this palliative can only be a short time measure, and however will encourage more nurses traveling abroad on the long run. Therefore, the hospital managers and government should provide a conducive working environment, better remuneration, attractive retirement benefit, and other incentives as a push in factor for nurses to stay back in their home countries.